Feminist Standpoint Theory: Conceptualization and Utility - Gurung, Lina (Dhaulagiri Journal of Sociology and Anthropology, 2020)
Feminist Standpoint theory challenges the notion of conventional scientific practices that had excluded women from the inquiry and marginalize them in every aspect of knowledge benefits and construction. Amidst the prevalent controversies, standpoint theorists have proposed alternative knowledge construction with the theses of ‘strong objectivity’, ‘situated knowledge’, ‘epistemic advantage’, and ‘power relations’. Feminist standpoint theory is claimed to be a successful methodology and the author support this argument based on the four reasons; the logic of discovery, insider-outsider position, study up, and methodological innovation. The author also put forwards the various challenges confronted by feminist standpoint theory and the justification given by the theorists. The cognitive, methodological, and epistemological interrogations toward this theory have widened its scope and adoption in social science research. The paper aims to suggest this analysis as the most suitable analytical and theoretical approach to do feminist inquiry which brings the understanding of feminist epistemologies as the most appropriate alternative approach of recent inquires against the dominant practices.